PERAN OTORITAS JASA KEUANGAN DALAM UPAYA PERLINDUNGAN HUKUM BAGI INVESTOR PASAR MODAL DI INDONESIA - La Ode Mbunai; Yusup Suparman (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The capital market has an important role in the modern economic system by providing a source of funding for companies and investment opportunities for the public. This research uses a normative juridical research method with a statutory approach. This research discusses the legal framework related to the role of the financial services authority in the capital market, specifically Law No. 8 of 1995 concerning the Capital Market and the establishment of the Financial Services Authority (OJK) based on Law No. 21 of 2011. The role of OJK is crucial in supervising and regulating the financial services sector, ensuring fair and transparent transactions to protect the interests of investors. This study analyses the importance of legal protection for investors, emphasising that effective regulation is essential to foster investor confidence and market integrity. In addition, this study also discusses dispute resolution mechanisms in the financial services sector, including the establishment of the Alternative Dispute Resolution Institution-Financial Services Sector (LAPS-SJK) to enhance consumer protection. Keywords: Financial Services Authority, Investor Legal Protection, Capital Market.   Abstrak: Pasar modal memiliki peran penting dalam sistem ekonomi modern dengan menyediakan sumber pendanaan bagi perusahaan dan peluang investasi bagi masyarakat. Penelitian ini menggunakan metode penelitian yuridis normatif dengan pendekatan paraturan perundang-undangan. penelitian ini membahas kerangka hukum terkait peran otoritas jasa keuangan dalam pasar modal, khususnya Undang-Undang No. 8 Tahun 1995 tentang Pasar Modal dan pembentukan Otoritas Jasa Keuangan (OJK) berdasarkan Undang-Undang No. 21 Tahun 2011. Peran OJK sangat penting dalam mengawasi dan mengatur sektor jasa keuangan, memastikan transaksi yang adil dan transparan untuk melindungi kepentingan investor. penelitian ini menganalisa pentingnya perlindungan hukum bagi investor, dengan menekankan bahwa peraturan yang efektif sangat penting untuk menumbuhkan kepercayaan investor dan integritas pasar. Selain itu, penelitian ini juga membahas mekanisme penyelesaian sengketa di sektor jasa keuangan, termasuk pembentukan Lembaga Alternatif Penyelesaian Sengketa-Sektor Jasa Keuangan (LAPS-SJK) untuk meningkatkan perlindungan konsumen. Kata Kunci: Otoritas Jasa Keangan, Perlindungan Hukum Investor, Pasar Modal.